Money markets and bank lending: Evidence from the adoption of tiering - Carlo Altavilla; Miguel Boucinha; Lorenzo Burlon; Mariassunta Giannetti; Julian Schumacher (European Central Bank (ECB), 2022)
Exploiting the introduction of the ECB's tiering system for remunerating excess reserve holdings, we document the importance of access to the money market for bank lending. We show that the two-tier system produced positive wealth effects for banks with excess reserves and encouraged a reallocation of liquidity toward banks with unused exemptions. This ultimately decreased the fragmentation in the money market and enhanced the monetary policy transmission mechanism. The increased access to money markets by banks with unused allowances incentivizes them to extend more credit than other banks, including banks with excess liquidity whose valuations increase the most.
Keywords: G2; E5; 330; Money market; bank lending; negative interest rate policy